Language and ethnicity in Central and Eastern Europe: Some theoretical aspects - Schopflin, George (Politologija, 2025)
This article presents a favourable theoretical analysis of the political problem of high profile which acutely touches Central and Eastern Europe – the ethnic problem. The outstanding role in delimiting ethnic dependence and conditioning ethnic cleavage turns to be devoted to language. The author gives a very persuasive introduction to this problem as well as promotes an exclusive comparison where the Western (arguably – civilly developed cultures) and Central-Eastern European nations, as well as history-influenced modifications to the character of the issue, are paralleled. We are not presented with a narrow and simplistic narration but are rather compelled to thoroughly perceive the multilateral complexity of this problem. Hence the author tries to trace the solutions that entail inter-ethnic tensions, although he primarily identifies the ’true’ causes for such tensions. Schopflin finds it necessary to define what exactly ethnicity is and the reasons why language is enacted to such a salient role in ethnic self-consciousness. He excludes the restrictive assumption that ethnicity has been made political by "artificial" means only, providing evidence of why this approach proves to be not exhaustive. A sharper insight into this problem is introduced. The essential point is that ethnicity operates simultaneously on several planes, only one of which belongs to the political one. The author argues that while in pre-modern societies there was no occurrence of the political system to impinge too directly on cultures, with the coming of modernity, it began to do so. The article foregoes with the clarification that ethnicity is about cultural reproduction, where culture is defined as a system of moral regulation in its deepest sense. Cultural variations which locate distinctions and peculiarities in the questions of political power come to constitute the raw material for ethnic cleavage, because each community is axiomatically convinced of the rightness of its morality and its superiority to all others. The author continues in the depiction of the characteristics which specify the Western cultures and the Eastern nationalisms in which the former proves to be the type of democratic nationalism, the one to nurture loyalties, whenever the latter managed to rear up an all-directing monopolical political elite (the author names them ’secular intellectuals’) who challenged every aspect of the established status quo and saw this as their raison d’être. Their vocation was not confined to some relatively confined arena (as in the West) but devoted themselves to nation-wide aspects, as the language might prove. In the face of the deprivation of the Western civic homogenisation, language in Central and Eastern Europe attained a much more effective basis for power than contiguity. Language in the latter became an instrument of popular mobilisation. Intellectuals used and controlled language; it became both instrument and aim; intellectuals consequently acquired paths to moral legislation. The author notices that any efforts to construct political nations on some other principles, namely geographical, in Central and Eastern Europe failed because of the lack of dynamism that derives from an authentically felt sense of community. Whenever the civic dimension of the nationhood devolves its primacy in the West, language demonstrates its primacy in the East. Expressive words of a Hungarian writer Gyula Illyes are put forward: if, he states, there is a language, then its speakers constitute a community; if a community has its own language, it has the right to constitute its own state and become a subject of history. The author concludes that language has played both a symbolic and a functional role in the centralisation of Central and Eastern Europe. It is claimed that though there can be no contingency in the nature of language, no language, with the exception of Polish, has had a continuous high cultural tradition. It is, however, posed that high cultural languages are vital both instrumentally and as legitimation. Nevertheless, motion to modernity distracts Central and Eastern European countries from the wide tolerance to multilingualism, which is understood as weakness that potentially threatens the future of the community. Hence, intolerance and oppression prevailing in the countries is the proof that the modern state has proved to be unable to assimilate ethnic minorities, once they have become conscious of their identity. Only the situation of one having its own language is taken as acceptable. Numerous examples are given to support these arguments. It is concluded that despite the feeling of something being missed, the provided factors constitute an explanatory framework for why it is so extraordinarily difficult to establish linguistic co-existence at the high cultural level in Central and Eastern Europe and why seemingly simple problems acquire an apparently applicable and deep-rooted insolubility.